Synthesis of a chitosan nanoparticle suspension and its protective effects against enamel demineralization after an in vitro cariogenic challenge - Taís Chaves MAGALHÃES; Natália Moreira TEIXEIRA; Renata Sobreira FRANÇA; Ângelo Márcio Leite DENADAI; Rogério Lacerda dos SANTOS; Hugo Lemes CARLO; Eliseu Aldrighi MUNCHOW; Fabíola Galbiatti de CARVALHO (University of São Paulo, 2021)
Abstract Objective Our study aims to synthesize, characterize, and determine the effects of a ChNPs suspension on human enamel after cariogenic challenge via pH-cycling. Methodology ChNPs were synthesized by ion gelation and characterized by Transmission Electron Microscopy (TEM) and Dynamic Light Scattering. Forty enamel blocks were divided into four groups (n=10/group): (i) ChNPs suspension; (ii) chitosan solution; (iii) 0.05% sodium fluoride (NaF) solution; and (iv) distilled water. Specimens were exposed to cariogenic challenge by cycling in demineralization solution (3 h) and then remineralized (21h) for 7 days. Before each demineralization cycle, the corresponding solutions were passively applied for 90 s. After 7 days, specimens were examined for surface roughness (Ra) and Knoop hardness (KHN) before and after the cariogenic challenge; % KHN change (variation between initial and final hardness), and surface topography by an optical profilometer. The data were analyzed by repeated-measures ANOVA, One-way ANOVA, and Tukey tests (α=0.05). Results TEM images showed small spherical particles with diameter and zeta potential values of 79.3 nm and +47.9 mV, respectively. After the challenge, all groups showed an increase in Ra and a decrease in KHN values. Optical profilometry indicated that ChNPs- and NaF-treated specimens showed uneven roughness interspersed with smooth areas and the lowest %KHN values. Conclusion The ChNPs suspension was successfully synthesized and minimized human enamel demineralization after a cariogenic challenge, showing an interesting potential for use as an oral formulation for caries prevention.